2011
DOI: 10.1128/aac.00670-10
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Carbapenems on Bacterial Load and Host Immune Response in aKlebsiella pneumoniaeMurine Pneumonia Model

Abstract: Doripenem is a carbapenem with potent broad-spectrum activity against Gram-negative pathogens, including antibiotic-resistant Enterobacteriaceae. As the incidence of extended-spectrum ␤-lactamase (ESBL)-producing Gram-negative bacilli is increasing, it was of interest to examine the in vivo comparative efficacy of doripenem, imipenem, and meropenem against a Klebsiella pneumoniae isolate expressing the TEM-26 ESBL enzyme. In a murine lethal lower respiratory infection model, doripenem reduced the Klebsiella lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 48 publications
(51 reference statements)
1
13
0
Order By: Relevance
“…An in vitro study 21 has concluded that the addition of doripenem with colistin is synergistic and suppresses those Klebsiella organisms that were resistant to colistin. A study conducted using a murine model for K. pneumoniae showed more rapid resolution with enhanced antibacterial activity of doripenem as compared to other carbapenems 22 . These studies including the present study warrant continuous surveillance of infection with Klebsiella organisms including the use of combination therapy with colistin.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study 21 has concluded that the addition of doripenem with colistin is synergistic and suppresses those Klebsiella organisms that were resistant to colistin. A study conducted using a murine model for K. pneumoniae showed more rapid resolution with enhanced antibacterial activity of doripenem as compared to other carbapenems 22 . These studies including the present study warrant continuous surveillance of infection with Klebsiella organisms including the use of combination therapy with colistin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, treating Klebsiella pneumoniae has become more difficult due to the worldwide increase in multidrug resistant strains, leaving only limited clinical treatment options [ 4 – 8 ]. In effect, about 80% of the nosocomial infections caused by K. pneumoniae are due to these multidrug-resistant strains; the incidence of ESBLs (extended-spectrum beta-lactamase) isolates ranges from 8% to 44% [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In preliminary studies, the 50% lethal dose (LD 50 ) of S129-42 for healthy female BALB/c mice was less than 30 CFU by intraperitoneal infection (data not shown), indicating that female BALB/c mice are susceptible to Salmonella infection. To determine the serum concentrations of ceftriaxone, ertapenem, doripenem, and meropenem in these mice, each drug was subcutaneously administered to healthy mice as a single dose as previously described: 100 mg/kg of body weight for ceftriaxone (1) and 50 mg/kg for ertapenem (34), doripenem (12), and meropenem (15). At 0.5, 1, 2, 4, 6, and 8 h postinjection, blood samples from six anesthetized mice per treatment group were collected by cardiac puncture.…”
Section: Methodsmentioning
confidence: 99%